Renewable Distributed Generation and its Impact in Rural India - Bharadwaj, Suranjana (International Journal of Computer Sciences and Engineering, 2019)
Despite many sincere attempts from the authorities to increase the quality of power supplied to the rural households of India, a large population of rural India is still remains power-deprived. To change this situation, renewable energy along with distributed generation can become a feasible solution. In this paper, an in-depth analysis of the potential of renewable distributed generation is presented to tackle this power crisis. It also takes into account the government initiatives taken so far and the challenges lying ahead in this field.